Analysis of Dietary Patterns and Level of Nutritional Knowledge with the Incidence of Anemia in Pregnant Women in the Work Area of Wanasari Community Health Center, Bekasi Regency - Amir, Aprima Yona; Rozyka, Fafelia; Herayono, Febby; Sari, Silvie Permata (Journal of Health Science and Medical Therapy, 2025)
Anemia in pregnant women is said to have the potential to endanger mother and child. For this reason, anemia requires serious attention from all parties involved in health services. This study aims to determine the relationship between diet and level of nutritional knowledge with the incidence of anemia in pregnant women in the Wanasari Community Health Center working area. This type of research is descriptive research with a cross-sectional approach. The population and sample in this study were pregnant women in the third trimester in the work area of ​​the Wanasari Community Health Center who were taken using total sampling technique. Data collection used questionnaires and Hb sahli. The variables studied were the incidence of anemia in pregnant women, eating patterns, and level of nutritional knowledge. Bivariate analysis used the chi square test (CI=95%, a=0.05). There are 39.2% of pregnant women experience anemia, 31.4% of pregnant women have poor eating patterns, and 35.3% of pregnant women lack nutritional knowledge. The results of statistical tests on the relationship between diet and the incidence of anemia show a value of P = 0.000 (p < 0.05), and the level of nutritional knowledge for the incidence of anemia shows a value of P = 0.000 (p < 0.05). Each variable in this study is related to the incidence of anemia. It is hoped that the public can know and understand the factors related to anemia and prevent anemia from pregnant women to childbirth and breastfeeding.